Over a million students use our free study notes to help them with their homework
93x+1 =(32 )(3x+1) =36x+2
Firstly, expand the left hand side of the equation out to produce: [7x-35=25-3x]. Bring all the x's to one side (to form 10x=60). Divide both sides by 10 to find the solution for x [x=60/10]. Therefore, x...
a+a+4 = -p/5a+2 = -p/10(a+2)sqaured = q/5 +4p sqaured/100 = q/5 +4p sqaured = 100(q/5 +4)implies p squared = 20q+400
When looking at factorising quadratic equations, the first approach should be to identify what is in front of the x term and the value of the c term, with the equation being in the form of y=A(x^2)+Bx+c.S...
(x/2) + 3x/(x+1) = 1x(x+1) + 6x = 2x + 2x2 + x + 6x - 2x = 2x2 + 5x - 2 = 0Using the quadratic formula,x1 = (-5+(29)1/2)/2x2 = (-5-(29)Answered by Emily D. • Maths tutor2487 Views
←
582
583
584
585
586
→
Internet Safety
Payment Security
Cyber
Essentials